Unwanted company : foreign investment in American industries - Crystal, Jonathan, 1965- (Cornell University Press, 2003)
"Unwanted Company examines the different ways in which important U.S. industries (including semiconductors, automobiles, steel, consumer electronics, telecommunications, and airlines) reacted to this new challenge. It focuses on the political responses of U.S.-owned firms to how Washington ought to regulate foreign direct investment and how it ought to treat foreign-owned firms in the United States